Improving Student Interests and Learning Outcomes With the Jigsaw Type Cooperative Learning Model Approach in Al Madinah Elementary School Students, Jember - darsan, darsan (Journal of Education Technology and Inovation, 2023)
The teacher has the responsibility to determine the success of teaching and learning in schools. In addition, the learning process in the classroom requires the application of learning models so that learning becomes more interesting for students. One of them is by using a jigsaw, with the aim of increasing student interest and learning outcomes. This research is a class action research (CAR). Data collection techniques were carried out using documentation, observation, interviews, questionnaires, and test methods. The results of this study indicate the application of the jigsaw cooperative learning model in practice there are 7 steps, namely, forming heterogeneous groups consisting of ± 4 people, each member in the group is given a different subtopic, forming expert groups, expert group discussions, distributing expert groups, explaining the material to the original group, presenting the results of the discussion and finally closing. The application of this type of jigsaw cooperative learning model can increase student interest and learning outcomes. This can be seen from the percentage of interest in cycle I of 64.0% and in cycle II of 84.3%. Whereas the percentage of learning outcomes in cycle I and cycle II increased by 22.2%, namely in cycle I by 61.1%, increased in cycle II to 83.3%, the results of the data were obtained from filling out the test questions